The Relationship Between Perception and Social Conflict in Society: Islam Hadhari in Malaysia - Darni Yusna; Reza Fahmi; Prima Aswirna (Asian Social Work Journal, 2020)
The research objectives: (1) Explain the history of the development of Islam in Malaysia. (2) Explain the picture of the spread of the standard positive perception of religious leaders and community members about Islam Hadhari. (3) Connecting between positive opinions of religious leaders and community members and their relation to social conflicts in Malaysia. The study used a quantitative approach. The population in this study was 200 people, of which 38 were religious leaders, and 152 were members of the community. The data collection technique was using a psychological scale. Data analysis technique using Pearson correlation. The results of this study found that generally, the positive perceptions of religious leaders and community members about Islam Nusantara and Islam Hadhari were classified as high while the social conflict during society is classified as low.